2004
DOI: 10.1108/02652320410530322
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Internet banking among sophisticated consumer segments in an advanced developing country

Abstract: This descriptive study was conducted to develop an understanding of consumers' attitudes and adoption of Internet banking among sophisticated consumers. Based on a random sample of academicians, demographic, attitudinal, and behavioral characteristics of Internet banking (IB) users and non‐users were examined. The analyses revealed significant differences between the demographic profiles and attitudes of users and non‐users. IB users were further investigated, and three sub‐segments were defined according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
3
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(181 citation statements)
references
References 40 publications
7
162
3
9
Order By: Relevance
“…Onay and Ozsoz (2013) described that with the increasing number of e-banking users, half of the 32 deposit banks provide e-banking services. In the past decade in China, e-banking develops sharply in developing countries (Akinci, Aksoy, & Atilgan, 2004). The research of Akinci et al indicated that regarding consumers' attitudes and adoption of e-banking, there were significant differences between e-banking users and non-e-banking users in terms of attitudinal properties, demographic profiles, and preferences for service delivery channels.…”
Section: Proposed Hypothesismentioning
confidence: 99%
“…Onay and Ozsoz (2013) described that with the increasing number of e-banking users, half of the 32 deposit banks provide e-banking services. In the past decade in China, e-banking develops sharply in developing countries (Akinci, Aksoy, & Atilgan, 2004). The research of Akinci et al indicated that regarding consumers' attitudes and adoption of e-banking, there were significant differences between e-banking users and non-e-banking users in terms of attitudinal properties, demographic profiles, and preferences for service delivery channels.…”
Section: Proposed Hypothesismentioning
confidence: 99%
“…It is supposed to facilitate convenient transactions and easy accessibility to information. 2,13,59,60 Technology has improved the service quality and encounters, 61 and consumers can have direct access to online banking from home, workplace, or any other place at their leisure. 62 Malone et al 63 state that the Internet has not only brought cost savings to the companies, but has also enhanced communication with the consumers.…”
Section: Online Banking Functional Attributesmentioning
confidence: 99%
“…The diffusion of new technologies with user-friendly service models is expected to improve the banking services. 2 The adoption of Internet-based models for transactions has led to ' virtualization ' , and affects the bank and consumer relationships. 3 Byers and Lederer 4 opine that consumer ' s preferences, attitudes and motives are governing factors for developing service delivery options.…”
Section: Introductionmentioning
confidence: 99%
“…Bauer and Colgan, 2001;Hughes, 2001;Li, 2001;Mols, 1999;White, 2001, 2000). The issue has produced numerous studies touching several aspects of online banking and its consequences (for more detailed summary of internet banking related studies see Akinci, Aksoy and Atilgan, 2004).…”
Section: Introductionmentioning
confidence: 99%